Anion vacancy distribution and magnetism in the new reduced layered Co(II)/Co(I) phase LaSrCoO3.5-x - Hayward, M; Rosseinsky, M (2000)
The new reduced K2NiF4 Co(II) phase, LaSrCoO(3.5-x), is prepared by reduction of the Co(III) containing LaSrCoO4 using H2 gas and the new hydride solid-solid reduction methods. The hydride route is superior in both crystallinity and control of phase purity and allows access to reduced phases containing substantial concentrations of Co(I). The anion vacancies are located within the MO2 planes of the K2NiF4 structure but do not prevent the onset of long-range antiferromagnetic order: the magnetic structure is refined using a noncollinear model consistent with the tetragonal crystal symmetry.